Globalisation of Technology (India Studies in Business and Economics,, 2018)
This book examines the globalisation of technology and innovation in the modern world. Enterprises globalise in several ways, e.g. by exporting, sourcing components and materials from other countries (B2B commerce), outsourcing, licensing their technologies and production, and foreign direct investments (FDI). Transaction costs and location advantages play a crucial role in selecting the bestmode of globalisation. A number of important questions - like what are the pull and push factors contributing to FDI, does outward FDI from a developing country like India contribute to participation in international production networks, and does FDI mitigate business cycle co-movements - keep cropping up in the growing body of knowledge on the globalisation of technology. This book addresses these issues, as well as the consequences of FDI - in particular,with regard to technology, productivity, and R&D spillovers. Issues related to innovations, R&D, intra-industry trade, and knowledge management are also discussed.